`Match load` construct in professional football: complexities and considerations - Dixon, B.; Alexander, J.; Harper, D. (BMJ Open Sport & Exercise Medicine, 2026)
The differentiation between training load and match load is an important consideration in applied practice, with the match load construct being used in athlete monitoring to inform training prescription and return to play decision-making post-rehabilitation. The term `match load` lacks a clear definition, and its complexity requires greater recognition. We propose a practical, conceptual framework for match load and influential contextual factors to consider within professional football that may impact a player`s match load. The aim of the article is to provide practitioners with definitions of match load categories and to guide future research that may help enhance the measurement and management of load to inform training and rehabilitation processes.